LEGAL REASONING BY JUDGES IN THE DECISION OF THE RELIGIOUS COURT IN THE DKI JAKARTA AREA REGARDING SHARIA FINANCING - Supardin, Muhammad Ikhlas; Mubarok, Jaih; Muslimin, JM; Nasril, Muhammad; Amir, Rahma (Institut Agama Islam Negeri Curup, 2025)
This study aims to analyze the differences in Religious Court rulings on Sharia economic cases based on judges' ijtihad in interpreting and constructing laws. The legal interpretation conducted by judges represents ijtihad in uncovering legal solutions to Sharia economic issues found in Religious Court rulings in the DKI Jakarta region from 2016 to 2022. Judges’ ijtihad in legal discovery employs various methods or approaches, resulting in differences in rulings. The conceptual approaches utilized in this study include the statute approach and the case approach. The data sources for this research comprise Religious Court decisions in the DKI Jakarta region from 2016 to 2022 concerning Sharia economic cases, including murabahah, musyarakah, mudarabah, and istisna contracts. The data analysis technique employed in this research is descriptive qualitative analysis. The findings of this study demonstrate that judges’ ijtihad in legal discovery is grounded in statutory regulations and various relevant legal sources. Judges’ legal reasoning in examining, adjudicating, and delivering rulings applies different interpretative methods or approaches, leading to variations in rulings on similar Sharia economic cases. The ijtihad or legal reasoning methods used by judges are categorized into juridical interpretation methods, including grammatical, systematic, and authentic interpretations. Additionally, teleological interpretation is the sole legal reasoning method used by judges as a contextual approach, incorporating empirical evidence based on statutory provisions.